Factors Affecting Perception of Extension Agents Towards Effective Social Media Utilization Behaviour - A. Shanmuka; V. Lenin, V. Sangeetha, L. Muralikrishnan, V. Ramasubramanian, Alka Arora (Indian Journal of Extension Education, 2022)
Changing times demand an in-depth analysis of the unexplored opportunities which social media offers. As extension agents are the front line of the extension and advisory services a study focused on analyzing their perception towards effective social media utilization behaviour and factors affecting their perception was carried on in the IT revolutionized Andhra Pradesh state during 2021. The survey method was used to collect data from 160 extension agents selected through a proportionate random sampling method from three districts namely Chittoor, Srikakulam, and Guntur of Andhra Pradesh. It was found that 51.88% of the extension agents had a neutral perception. It was found that scientific orientation, job perception, technology management orientation, innovative proneness, information management orientation, and orientation towards the extension service profession of the extension agents had a significant and positive correlation with the perception. Stepwise regression analysis revealed that eight variables namely technology management orientation, orientation towards extension service profession, innovative proneness, scientific orientation, perceived workload, education, gender, and work experience, were a good fit with an R-square of 55.1 per cent.